A national-scale GIS-based system for modelling impacts of land use on water quality. (December 2016) - Elliott, Alexander H.; Semadeni-Davies, Annette F.; Shankar, Ude; Zeldis, John R.; Wheeler, David M.; Plew, David R.; Rys, Gerald J.; Harris, Simon R.
Abstract: Management of freshwater quality requires modelling tools for rapid evaluation of land use and management scenarios. This paper presents the CLUES (Catchment Land Use and Environmental Sustainability) model to address this need. CLUES provides steady state, spatially distributed, integrated catchment models tightly coupled to GIS software to predict mean annual loads of total nitrogen, total phosphorus, sediments and E. coli, and concentration of nutrients throughout New Zealand (268, 000 km 2 ) with a subcatchment resolution of 0.5 km 2 . CLUES also estimates potential nutrient concentrations for estuaries and provides key farm socio-economic indicators. The model includes a user interface for study area selection, scenario creation, data geo-visualisation, and export of results. It is pre-populated with spatial data and parameter values for New Zealand. Evaluation of the model and a summary of applications demonstrate the tractability and utility of national-scale rapid scenario assessment tools within a GIS framework. Graphical abstract: Highlights: Stream water quality prediction at mean annual time-scale throughout New Zealand at kilometre-scale resolution. Rapid scenario generation and evaluation of land use change and management measures (mitigation factors, intensification). Includes links to an estuary nutrient component and simple socio-economic indicators. Has a growing number of applications for catchment, regional and national scenario assessment.